Error-prone bypass of certain DNA lesions by the human DNA polymerase κ - Ohashi, Eiji (Cold Spring Harbor Laboratory Press, 2000)
The Escherichia coli protein DinB is a newly identified error-prone DNA polymerase. Recently, a human homolog of DinB was identified and named DINB1. We report that the DINB1 gene encodes a DNA polymerase (designated polκ), which incorporates mismatched bases on a nondamaged template with a high frequency. Moreover, polκ bypasses an abasic site and N-2–acetylaminofluorene (AAF)-adduct in an error-prone manner but does not bypass a cis–syn or (6-4) thymine–thymine dimer or a cisplatin-adduct. Therefore, our results implicate an important role for polκ in the mutagenic bypass of certain types of DNA lesions.